The process-reactive dimension and its relationship to thought disturbance in schizophrenia - Anderson, Roderick B H (Department of Psychology, 2016)
The intention of the present study is (a) to attempt to assess the relative merits of three contradictory models of thought disturbance in schizophrenia, and to effect (b) a reconciliation of these models by recourse to proposed differences in the scanning functions of process and reactive schizophrenics. The main hypotheses to be examined are as follows : (1) Schizophrenic patients as a whole should be pathologically susceptible to the effects of associative interference, whilst non-psychotic but psychiatrically disturbed persons and normals should reveal no such susceptibility. (2) Process schizophrenics should make significantly more stronger meaning response errors on Chapman et al.'s 1964 Lexical Ambiguities Test than either reactive schizophrenics, non-psychotic psychiatric patients or normals. (3) Process schizophrenics should have significantly shorter response latency times on Chapman et al.'s 1964 Lexical Ambiguities Test than reactive schizophrenics, non-psychotic psychiatric patients or normals. This latter hypothesis reflects a corollary to the concept of an interference reduction defense system amongst process patients. Response latency times have been employed as a rough measure of the extent of cognitive scanning. If process patients do discontinue scanning and editing early on in the two-stage process they should make their judgements sooner than reactives, and possibly normals and other psychiatric patients.